Comparative Analysis of Plate Girder Designs In The Composite Bridge Between AASHTO LRFD Bridge Design Specifications 2017 Regulation with SNI 1729: 2015 - Donald Essen; Ryza Nur Rohman (Journal of Applied Science, Engineering, Technology, and Education, 2019)
In the world of construction there are various methods and types of materials used to support the passage of a construction work. One of them is composite girder plate. Composite girder plate is one of the many construction methods that combine two construction materials that are physically different in nature, namely concrete with steel. This type of composite girder plate construction is commonly used for bridge construction work with a fairly large span and width. In its use, of course, it must be preceded by stages of careful planning on a standard and valid basis as well. In the following research will discuss and look for similarities and differences regarding the two types of rules in the planning of composite girder plates, namely the rules of planning composite girder plates using AASHTO LRFD BRIDGE DESIGN SPECIFICATIONS 2017 with SNI 1729: 2015. After doing the initial stages of modeling using CSI Bridge software using the profile cross section constraints of the AASHTO provisions, the internal force obtained is Moment Force (Mu) of 3469.13 kNm and Shear Force (Vu) of 225.98 kNm. Then proceed with the analysis of calculations with the help of Microsoft Excel software namely calculating using the AASHTO LRFD BRIDGE DESIGN SPECIFICATIONS 2017 regulations for stability requirements of strong boundary conditions on the bending requirements. Then a Nominal Moment (ØMn) value of 6420.19 kNm is obtained. Then proceed to calculate the same planning constraints, but this time using SNI 1729: 2015 regulations. Obtained Nominal Moment Value (ØMn) of 6579.88 kNm. Then it can be concluded that the two regulations produce a safe and strong planning, of course in accordance with applicable regulations namely: Moment (Mu <ØMn).